PSD2 ja sen vaikutukset verkkomaksamisen tietoturvaan ja liiketoimintamalleihin - Korhonen, Kai (2016)
Web payments have created a whole industry around them in the last decade where sensitive data is moved around and where security is one of the key concepts. On top of internal facilities, members of the EU are regulated by EU directives of which the second will be taken to legislation by the start of year 2017. It forces the banks to open interfaces that allow third parties to use web shop customers banking credentials in order to initiate payments.